THE PROBLEM OF THE RE-EXISTENCE OF MPR DECREES AS A TYPE AND HIERARCHY OF LEGISLATION IN INDONESIA - Made Gerry Gunawan; I Nyoman Bagiastra (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The Decree of the People's Consultative Assembly, also known as MPR Decrees, contains decisions made by the People's Consultative Assembly. The presence of MPR Decrees has undergone various system dynamics within the hierarchical order of legislation in Indonesia. Law Number 12 of 2011 on the Formation of Legislation reintroduces MPR Decrees as a type and hierarchy of law and regulation, reversing the previous law, Law Number 10 of 2004, which abolished the MPR Decrees from the structural hierarchy. The re-existence of MPR Decrees in the Indonesian legislative system has implications for the order and position of these decrees in the state administration system. This research adopts a normative research method, utilizing a statutory approach as the primary legal material and secondary legal materials such as books, journals, and other sources for analysis. The findings of this study indicate that the re-existence of MPR Decrees creates ambiguity in the validity of the MPR within the state administration system, considering that MPR Decrees originated before the reform or amendment of the 1945 Constitution, when the MPR held a higher position as a state institution. Furthermore, there is no authorized judicial institution to test the MPR Decrees if they are suspected of violating the provisions of the Constitution of the Republic of Indonesia.